MENINGKATKAN KEMAMPUAN MEMBACA PUISI SISWA DENGAN MENGGUNAKAN MEDIA PEMBELAJARAN AUDIO VISUAL TEMA CITA-CITAKU PADA SISWA KELAS IV SD NEGERI 105326 BANGUN REJO - Dhea Ramadhani; Nurjannah (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
This research aims to describe the results of the ability to read poetry by using audiovisual learning media on the theme of my dreams of grade IV students of SDN 105326 Bangun Rejo. This type of research is Classroom Action Research which consists of 4 stages, namely planning, implementation, observation, and reflection. Researchers used an instrument in the form of a poetry reading ability test consisting of vocal, intonation, rhythm, visualization, and expression assessments. The subjects of this study consisted of 32 fourth grade students of SDN 105326 Bangun Rejo in the 2022-2023 academic year. The results showed that the use of audiovisual learning media on the ability to read poetry of grade IV students of SDN 105326 Bangun Rejo increased from pre-research, cycle I, to cycle II. In the pre-research, 20 students achieved learning completeness while 12 other students had not yet reached completion, with the percentage of completeness reaching 57.14%; cycle I classical learning completeness reached 23 students completed, 9 other students did not complete, with the percentage of completeness reaching 65.71%; In cycle II learning completeness reached 27 students completed, 5 students did not complete, and the percentage of completeness reached 84.38%. Thus, it can be concluded that using audio-visual media can improve the reading skills of poetry on the theme of my dreams of fourth grade students of SD Negeri 105326 Bangun Rejo.